THE INFLUENCE OF LEARNING STYLE ON MATHEMATICS LEARNING ACHIEVEMENT AMONG 10TH GRADE STUDENTS OF MAN 4 CENTRAL MALUKU, INDONESIA - Ernawati Ernawati; Surima Sahirun; Ahmad Fajarisma Budi Adm (Universitas Brawijaya, 2021)
This study examined the influence of learning styles on mathematics learning achievement of 10th grade students in MAN 4, Central Maluku. Learning styles included visual learning style, auditory learning style, and kinesthetic learning style. This ex-post facto study was conducted using a quantitative approach, which data were analyzed using multiple linear regression analysis. This study was conducted from April 2 to April 9 2018 in MAN 4, Central Maluku. The population in this study amounted to 57 students consisting of 2 classes, namely class X MIA and X IIS. Samples were selected from the whole population. Questionnaires and documentation were used as data collection instruments. The results of the data analysis showed a positive relationship between learning styles on learning achievement, with a value of 0.060 and an effect of 0.4%. Even though the influence was weak, learning styles still influence students' mathematics learning achievement. Since the significance value was set at > 0.05, H0 was accepted and H1 was rejected. Therefore, learning styles had no significant influence on the mathematics learning achievement of 10th grade students in MAN 4 Central Maluku.